Science Trail: a pathway of Scientific Education in Príncipe Island - Latas, J. (2015)
Framed in an integrated vision of formal and non-formal educational contexts, the pathway of scientific education in Príncipe Island - Science Trail, was conceptualized, implemented and assessed. Science Trail provides the contact with nature and assumes the exploration of scientific contents, integrated in a historical and cultural Principean context. Moreover, cultural contexts have multidisciplinary potentialities which, when recognized and legitimated, enhance a holistic view of Science (Gerdes, 2007). In particular, some of those cultural and historical contexts proved to be facilitators in the process of building bridges with mathematical concepts, enhancing connections between Culture and Mathematics. The drawing up of this trail was the responsibility of a multidisciplinary team of Principe’s High school teachers and its implementation targeted mainly high school students. The evaluation of the Science Trail, namely its impact on participants, based on data gathered through questionnaires and document compilation, points to the continuity of this initiative and to the recognition of its educational potentialities.